Optimization of Starch—κ-Carrageenan Hybrid Film as Drug Delivery System Using Response Surface Method - Nisah, Khairun; Fahrina, Afrilia; Rizki, Diva Rayyan; Puspita, Kana (Heca Sentra Analitika, 2023)
Development of drug delivery systems (DDS) has been widely carried out using safe biopolymers – starch and κ-carrageenan. However, for optimal use, the foregoing polymers still suffers from mechanical weakness. Combining both polymers could enhance the properties of each of the polymer. This research aimed of improving the applicability of starch and κ-carrageenan as DDS by means of polyelectrolyte complexation to form a polymer film. The composition ratio of starch:κ-carrageenan was optimized using response surface method (RSM) on Design Expert 11.0 based on water swelling, tensile strength, and disintegration time of the film. Fourier transform infrared spectrometry was performed on the prepared starch—κ-carrageenan film and suggested the successful film preparation. The bulk characteristics of the film are dependent on the starch or κ-carrageenan composition ratio, where starch has been associated with higher thickness, while κ-carrageenan — rigidity. From the RSM, the optimized composition was revealed to be 2.95 and 2.84 g for starch and κ-carrageenan, respectively, in a 60 mL aqueous solvent. The predicted optimum properties of the film were 160.21%, 3.26 MPa, and 17.47 min for swelling degree, tensile strength, and disintegration time, respectively. Taken altogether, the characteristics of starch or κ-carrageenan individually could be modified by polymeric combination, where they could be optimized by means of RSM.